A novel apparatus for in situ compression of submicron structures and particles in a high resolution SEM - Romeis, Stefan; Paul, Jonas; Ziener, Marc; Peukert, Wolfgang (Review of Scientific Instruments, 2012)
We report on the development and characterization of a novel in situ manipulation device to perform stressing experiments on the submicron scale inside a high resolution field emission scanning electron microscope. The instrument comprises two main assembly groups: an upper part for positioning and moving a mounted probe and a force sensor as well as a specimen support as lower part. The upper part consists of a closed loop tripod piezoelectric scanner mounted on a self-locking coarse positioning stage. Two interlocked steel springs and a linear variable differential transformer measuring the springs’ deflections compose the lower part of the instrument. This arrangement acts as force-sensor and sample support. In comparison to already well-established concepts a wide measuring range is covered by adjusting the spring constant between 30 N/m and 50000 N/m. Moreover, the new device offers striking advantages with respect to force calibration and sample deformation measurements. Force calibration is performed using the eigenfrequency of the force detection system directly inside the SEM. Deformation data are obtained with high accuracy by simultaneously recording displacements above and below the specimen. The detrimental apparatus compliance is determined, and the influence on measured data subsequently minimized: an easy to validate two-springs-in-series model is used for data correction. A force resolution in normal direction of 100 nN accompanied by a sample deformation resolution of 5 nm can be achieved with the instrument using an appropriate load cell stiffness. The capabilities and versatility of this instrument are exemplified by compression experiments performed on submicron amorphous silica particles.

A review of models for single particle compression and their application to silica microspheres - Paul, Jonas; Romeis, Stefan; Tomas, Jürgen; Peukert, Wolfgang (Advanced Powder Technology, 2014)
We report on the deformation behavior of single silica microspheres. For the first time a detailed discussion on the quantitative evaluation of force–deformation data in the elastic and plastic regime is given. The microspheres are compressed between two flat plates of a custom built manipulation device supported by a scanning electron microscope. The device allows a high sample throughput enabling full statistical evaluation of force–deformation data of single microspheres. Existing theories describing the deformation behavior of single spheres are discussed and applied to the elastic and plastic deformation regime of silica microspheres. The results obtained from the theories are compared between each other and values reported in literature. The silica microspheres exhibit a significantly different deformation behavior than expected from bulk fused silica, i.e. a distinct plastic deformation behavior. Furthermore, a significant decrease in Young’s modulus and hardness was observed caused by high porosity and reduced crosslinking of silicon atoms, respectively, that is inherent to silica produced by Stöber synthesis. However, the calculated contact pressures exceed the compressive strength of bulk fused silica by at least a factor of two as an effect of a reduced amount of material flaws in microstructures.

Correlation of Enhanced Strength and Internal Structure for Heat-Treated Submicron Stöber Silica Particles - Romeis, Stefan; Paul, Jonas; Hanisch, Mathias; Marthala, Venkata; Hartmann, Martin; Klupp Taylor, Robin; Schmidt, Jochen; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2014)
The Stöber–Fink–Bohn (SFB) method allows the synthesis of spherical silica particles over a wide size range. Owing to the complex formation mechanism, the internal structure and related mechanical properties are not well understood. Within this account, the internal structure of synthesized SFB particles is changed systematically by heat treatments. Characterization by colloid titration, infrared spectroscopy, and solid-state nuclear magnetic resonance spectroscopy and the assessment of mechanical properties for single particles by in situ micromanipulation shed light on structure–property relations. Over the course of heat treatment, SFB particles become denser and owing to condensation of internal hydroxyl groups, the cross-linking of the silica network is enhanced. The observed chemical and structural changes are reflected by the mechanical properties of the particles: starting from a low Young’s modulus and hardness, clearly below the bulk properties of fused silica, both values are increasing over the course of the thermal treatment. Hardness for fused silica is approached after a treatment at 800 °C and exceeded after a treatment at 1000 °C. Young’s modulus approaches the bulk value. Furthermore, a significant plasticity is found: the sustained deformations are extremely high, and thus silica spheres with enhanced strength have been obtained by the thermal treatment.

Deformation behavior of micron-sized polycrystalline gold particles studied by in situ compression experiments and frictional finite element simulation - Paul, Jonas; Romeis, Stefan; Herre, Patrick; Peukert, Wolfgang (Powder Technology, 2015)
We present a combined experimental and finite element study on the deformation behavior of micron-sized polycrystalline gold particles. This study enables detailed insights into the underlying deformation mechanisms of the particles. Scanning electron microscope supported in situ uniaxial compression experiments of the single spherical polycrystalline gold particles were performed in the size range of 1. μm by using a custom built manipulation device. By testing a large number of particles stress-strain data and information on the particle morphology were obtained with statistical significance. The experimentally observed stress-strain behavior and the geometric shape of the stressed particles were found to be in excellent agreement with the elastic-perfectly plastic finite element model accounting for frictional effects at the contact interfaces. A significantly increased yield strength compared to bulk gold was found - grain size strengthening according to the Hall-Petch relation was identified as the main hardening mechanism. Hardness was found to vary with strain - an effect related to the altering geometric shape of the particles during compression. Comparison to a frictionless finite element model revealed the necessity of considering the effect of friction. These findings are not restricted to gold particles, but should be applicable to a wide range of elastic-perfectly plastic materials.
Keywords: FEM; Friction; Gold particles; In situ SEM; Mechanical properties

Deformation behavior of nanocrystalline titania particles accessed by complementary in situ electron microscopy techniques - Herre, Patrick; Romeis, Stefan; Mackovic, Mirza; Przybilla, Thomas; Paul, Jonas; Schwenger, Jan; Torun, Boray; Grundmeier, Guido; Spiecker, Erdmann; Peukert, Wolfgang (Journal of the American Ceramic Society, 2017)
Keywords: mechanical properties; titanium oxide; transmission electron microscopy; nanoparticles; scanning electron microscopy

Deformation behavior of nanocrystalline titania particles accessed by complementary in situ electron microscopy techniques - Herre, Patrick; Romeis, Stefan; Mackovic, Mirza; Przybilla, Thomas; Paul, Jonas; Schwenger, Jan; Torun, Boray; Grundmaier, Guido; Spiecker, Erdmann; Peukert, Wolfgang (Journal of the American Ceramic Society, 2017)
The mechanical behavior of nanostructured spherical submicrometer titania parti- cles was studied by in situ uniaxial compression experiments in the scanning and transmission electron microscope (SEM and TEM). Mesoporous and amorphous titania particles were prepared by a wet chemical sol-gel approach. To obtain nanocrystalline (nc) single-phase anatase and rutile particles the amorphous parti- cles were cryst allized by high-temperature annealing. For each sample the defor- mation behavior of at least 50 particles was investigated by in situ compression experiments in the SEM. In all cases an elastic – predominantly plastic deforma- tion behavior accompanied by crack initiation at exceptionally high engineering strain values of several percent were observed. Crack propagation presumably along grain boundaries and a Weibull distributed fracture stress was shown for all nc particles. Complementary in situ TEM experiment s and ex situ analysis of focused ion beam prepared particle cross-sections were carried out to identify the underlying deformati on mechanisms. Grain rotations and grain sliding are observed for nc anatase particles during in situ compr ession and are further identi- fied to be linked to a densification of the mesoporous particle structure. Our dedi- cated prepar ation and quanti tative in situ characterization methodology provides an excellent basis for a better understanding of the mechanical behavior of advanced ceramics.
Keywords: mechanical properties; nanoparticles; scanning electron microscopy; titanium oxide; transmission electron microscopy

Effects of an adhesive force of admixed particles on compressed packing fractions in a particle bed - Peukert, Wolfgang; Paul, Jonas; Koch, Thomas; Yoshida, Mikio; Sanagawa, Tomoya; Okano, Shun-ichiro; Oshitani, Jun; Yamamoto, Hiroaki; Gotoh, Kuniaki (Advanced Powder Technology, 2015)
One of the techniques for a reduction in particle cohesiveness is the admixing of nano-particles. However, the mechanism of cohesiveness reduction has not yet been clarified. In this study we focused on a compressed packing fraction as one of the values reflecting the cohesiveness and flowability in a compressed particle flow. In order to estimate the mechanism of the reduction, the effects of an adhesive force of admixed particles on the packing fraction were investigated experimentally. In the experiments, silica particles with 397 and 8 nm diameters were used as the main and the admixed particles, respectively. The surfaces of the admixed particles were modified chemically in order to vary their adhesive force with maintaining morphological and mechanical characteristics. At more than 2.0% mixing mass ratios, the decreasing rate with increasing the mass ratio in net difference value of packing fraction for modified admixed particles was smaller than that for the raw particles. A calculation of the packing fraction of the admixed particles in the voids of main particles revealed that difference of the decreasing rates could be attributed to the difference of cohesivenesses between raw and modified admixed particles. The maximum packing fraction achieved by the modified admixed particles was lower than that achieved by the raw admixed particles. However, when a mixture of main and admixed particles was packed by tapping, the packing fraction with modified admixed particles was higher than that with raw admixed particles. This implied that the adequate adhesive force of admixed particles is different by the applied compression force value.
Keywords: Admixture of nano-particles; Chemical surface modification; Compressed particle bed; Packing fraction

Indentation and Self-Healing Mechanisms of a Self-Assembled Monolayer-A Combined Experimental and Modeling Study - Meltzer, Christian; Paul, Jonas; Dietrich, Hanno; Jäger, Christof; Clark, Timothy; Zahn, Dirk; Braunschweig, Björn; Peukert, Wolfgang (Journal of the American Chemical Society, 2014)
A combination of in situ vibrational sum-frequency generation (SFG) spectroscopy and molecular-dynamics (MD) simulations has allowed us to study the effects of indentation of self-assembled octadecylphosphonic acid (ODPA) monolayers on α-Al2O3(0001). Stress-induced changes in the vibrational signatures of C-H stretching vibrations in SFG spectra and the results of MD simulations provide clear evidence for an increase in gauche-defect density in the monolayer as a response to indentation. A stress-dependent analysis indicates that the defect density reaches saturation at approximately 155 MPa. After stress is released, the MD simulations show an almost instantaneous healing of pressure-induced defects in good agreement with experimental results. The lateral extent of the contact areas was studied with colocalized SFG spectroscopy and compared to theoretical predictions for pressure gradients from Hertzian contact theory. SFG experiments reveal a gradual increase in gauche-defect density with pressure before saturation close to the contact center. Furthermore, our MD simulations show a spatial anisotropy of pressure-induced effects within ODPA domains: molecules tilted in the direction of the pressure gradient increase in tilt angle while those on the opposite side form gauche-defects.
Keywords: spectroscopy; monolayer; self-assembly

In situ cracking of silica beads in the SEM and TEM - Effect of particle size on structure-property correlations - Paul, Jonas; Romeis, Stefan; Mackovic, Mirza; Marthala, Venkata; Herre, Patrick; Przybilla, Thomas; Hartmann, Martin; Spiecker, Erdmann; Schmidt, Jochen; Peukert, Wolfgang (Powder Technology, 2015)
Stöber Fink Bohn (SFB) silica is a well-known colloidal system: monodisperse spherical particles are readily obtained by this wet chemical synthesis route. Despite the frequent application of SFB silica, its mechanical properties are not comprehensively understood. Within this account, size dependent mechanical properties of single SFB particles are systematically investigated using in situ SEM and TEM techniques: particle properties are addressed in the size range of 1.5 μm down to 200 nm. Both, untreated particles and heat treated particles densified at 1000 °C are investigated. Structural characterization by vibrational spectroscopy, by solid state nuclear magnetic resonance spectroscopy, by scanning electron microscopy and by focused ion beam machining allows correlating mechanical properties and the internal particle structure. For untreated particles comprised of a weakly cross-linked silica network a high degree of plasticity associated with low Young’s moduli and hardness values is found. At large strains only cracking without full fracture of the particles occurs, whereby the crack path is clearly linked to the synthesis conditions: for larger particles obtained from a multistep growth process cracks propagate along weak intraparticle interfaces and are deflected around an inner core structure. After the thermal treatment cross-linking of the silica network is significantly enhanced and Young’s moduli comparable to vitreous silica accompanied by increased hardness values are found. Only the smallest particles exhibit cracking; fracture into two or more pieces is distinguished for particles above 500 nm. It is found by SEM imaging that the relative occurrence of cracking into several pieces is increasing with size - a behaviour associated with the brittle to ductile transition of silica. By testing a large quantity of particles, statistical significance is ensured.

In situ deformation and breakage of silica particles inside a SEM - Romeis, Stefan; Paul, Jonas; Herre, Patrick; Hanisch, Mathias; Klupp Taylor, Robin; Schmidt, Jochen; Peukert, Wolfgang (7th World Congress on Particle Technology, WCPT 2014, 2015)
Mechanical properties and particle breakage behavior in the submicron size range are of fundamental importance for many particle related processes and applications. Although many (in situ) studies have been dedicated to materials' size dependent mechanical characterization, particles as free standing structures have been omitted widely. An important, yet open question is the structure property relationship at small scales. Within this account, the application of a custom built manipulator for particle compression inside a scanning electron microscope (SEM) is presented: Stöber-Fink-Bohn (SFB) particles with mean diameters of 500 nm and 1000 nm are subjected to heat treatments and their mechanical properties are directly correlated to the internal structure. The as-synthesized SFB particles exhibit a complex and size dependent internal structure. Mechanical properties undermatching the values of fused silica are found and only plastic cracking at large strains is observed: cracks are formed at the surface and propagate in radial direction towards the particle center. Heat treatment leads to densification. The degree of changes is controlled by temperature and treatment time. Starting from initially low values, Young's modulus and hardness are increasing with treatment temperature. Properties of fused silica are approached or even exceeded after a treatment at 1000°C. A significant level of plasticity and high sustained deformations are still found. Whereas small particle show ductile cracking, the heat treated micron sized particles show a brittle behavior. A brittle to ductile transition in the size range of 500 nm to 1000 nm is thus identified.
Keywords: heat treatment; in situ manipulation; mechanical properties; Stöber silica; Submicron particles

Local densification of a single micron sized silica sphere by uniaxial compression - Romeis, Stefan; Paul, Jonas; Herre, Patrick; de Ligny, Dominique; Schmidt, Jochen; Peukert, Wolfgang (Scripta Materialia, 2015)

Lubrication of Individual Microcontacts by a Self-Assembled Alkyl Phosphonic Acid Monolayer on α-Al2O3(0001) - Paul, Jonas; Meltzer, Christian; Braunschweig, Björn; Peukert, Wolfgang (Langmuir, 2016)
We report on the tribological behavior of a self-assembled alkyl phosphonic acid monolayer on the microscale using the colloidal probe technique. Friction-load data and adhesion forces were measured with borosilicate glass particles on uncoated and octadecylphosphonic acid (ODPA) coated α-AlO(0001) surfaces. A significant decrease in friction force was observed after surface coating, while the adhesion force was only moderately reduced. We assume the lubrication effect of the ODPA self-assembled monolayer (SAM) to be close to the maximum obtainable of alkyl phosphonic acids in the studied system due to the high molecular order which was confirmed by vibrational sum-frequency generation. At small loads, a nonlinear dependence of friction force to load was maintained after surface coating. However, a shift from a contact behavior well described by the DMT model toward the JKR model occurred that is possibly related to the altered elastic properties of the coated surface. With increasing load, a linear friction-load behavior was observed on the coated samples. Molecular plowing and adhesive interactions were identified as responsible mechanisms. In all friction experiments, we could not detect any wear neither of the colloidal probes nor at the surfaces of uncoated and coated samples. This proves the high wear resistivity of the studied ODPA SAM.

Mechanical particle properties - design, characterization and application - Romeis, Stefan; Peukert, Wolfgang; Paul, Jonas (International Conference for Conveying and Handling of Particulate Solids (CHoPS2015), 2015)
The (nano-)mechanics of particles across all length scales down to the nanoscale are highly relevant for many applications including adhesion, friction, powder flow, comminution and tribology. Nanomechanical elastic and inelastic particle properties have been measured systematically in a novel nanoindentation device installed within a scanning electron microscope to obtain simultaneously forcedisplacement information and optical images of deformed and broken particles. Quantitative data of intrinsic particle properties (and their respective distributions) are measured for oxide, metal and polymer particles. We discuss structure - property functions of particles in a quantitative way for selected applications, e.g. the production of bioactive glass and novel polymer particles in additive manufacturing.
Keywords: nano; mechanic; particle; powder; flow